Fa’aaliyyah Tathbiiq al-Wasaail al-Sam’iyyah al-Syafahiyyah li Tarqiyyah Mahaarah al-Kalam lada Thullaab Madrasah As’ad al-Mutawassithah al-Islaamiyyah bi Madinah Jambi - Arnindio Maulidika Yurman; Badrul Islam; Uril Bahruddin (UIN Maulana Malik Ibrahim Malang, 2023)
Teaching aids have an important role in achieving educational goals, but teachers and students face problems in applying educational aids because of machine challenges. In order to create effective learning, teachers need to use teaching aids that can capture students' interest so that students can immediately gain meaning during the learning process. The aim of this research is to find out the effectiveness of applying audio and verbal means to improve the speaking skill of the students of Asaad Intermediate Islamic School in Jambi. As for the entrance to this research, it is quantitative research with the type of objective statistics, and the method used is experimental research and data collection and analysis using the Phi coefficient using random testing, homogeneity testing, and normality testing. Based on calculations using a t-test done like this 0,05 8 0,40 So Ha received, this means that there is a significant difference between the speech skills of students who use auditory-verbal aids and those who do not use auditory-verbal aids. The conclusion of this research indicates that audio-oral means are necessary in promoting speaking skill.